Prologue: Peritoneal Dialysis in Pakistan: A Journey Just Started. - Khan, Qamar (Pakistan Journal of Kidney Diseases, 2021)
I was asked to write on recent initiatives taken to promote peritoneal dialysis (PD) in Pakistan. I will try to take you through this journey that led us here, that is in establishing PD as a viable and reasonable alternative to hemodialysis (HD) in a subset of end stage renal disease (ESRD) patients.